2007
DOI: 10.1097/fpc.0b013e32801a3be6
|View full text |Cite
|
Sign up to set email alerts
|

A splice site polymorphism in the G-protein β subunit influences antidepressant efficacy in depression

Abstract: These results suggest that inheritance of the GNB3C825T allele may significantly influence antidepressant response and emphasises the potential importance of polymorphisms in genes in signalling cascades activated by commonly prescribed antidepressants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 57 publications
2
46
2
Order By: Relevance
“…Genetic polymorphisms CREB1 polymorphisms have been associated with mood disorders, mainly exhibiting a significant gender effect (Zubenko et al 2003a(Zubenko et al , 2003bPerlis et al 2007;Dong et al 2009;Utge et al 2010;Juhasz et al 2011;Lazary et al 2011), nevertheless not unequivocally (Burcescu et al 2005;Hettema et al 2009). Findings for CREB1 and antidepressant response are also inconsistent (Murphy et al 2004;Wilkie et al 2007;Serretti et al 2011;Calati et al 2013) and negative findings have also been reported (Dong et al 2009;Crisafulli et al 2012;Matsumoto et al 2014).…”
Section: Cyclic Amp Response Element Binding Proteinmentioning
confidence: 78%
“…Genetic polymorphisms CREB1 polymorphisms have been associated with mood disorders, mainly exhibiting a significant gender effect (Zubenko et al 2003a(Zubenko et al , 2003bPerlis et al 2007;Dong et al 2009;Utge et al 2010;Juhasz et al 2011;Lazary et al 2011), nevertheless not unequivocally (Burcescu et al 2005;Hettema et al 2009). Findings for CREB1 and antidepressant response are also inconsistent (Murphy et al 2004;Wilkie et al 2007;Serretti et al 2011;Calati et al 2013) and negative findings have also been reported (Dong et al 2009;Crisafulli et al 2012;Matsumoto et al 2014).…”
Section: Cyclic Amp Response Element Binding Proteinmentioning
confidence: 78%
“…302 The GNB3 (825)T variant was found to predict a better antidepressant response in 5 independent studies. 170,[303][304][305][306] Lack of association has also been found. 83,307,308 Hypothalamic-pituitary-adrenal axis and stress hormone system Dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis is one of the most robust findings in many patients with MDD (up to 70%).…”
Section: Intracellular Signal Transduction Pathwaysmentioning
confidence: 95%
“…Because G proteins are involved in the signaling cascades of more than a thousand different receptors, complex phenotypes in association with the G␤3 rs5443 alleles have been described, although not without controversy (for review, see Siffert, 2005). Variants in GNB3 have also been attributed to pharmacogenomic effects, particularly on adrenergic and serotonergic mechanisms (Hauner et al, 2003;Schü rks et al, 2007;Wilkie et al, 2007). With regard to ARs, intracoronary administration of the ␣ 2 -AR agonist azepexole was associated with increased vasoconstriction in carriers of the 825T allele compared with persons with the wild-type C variant (Table 5) (Baumgart et al, 1999).…”
Section: Pharmacogenomics Of Gpcr Ligands In Cardiovascular Medicinementioning
confidence: 99%